Connecting the Properties of Coronal Shock Waves with Those of Solar Energetic Particles - Kouloumvakos A; Rouillard AP; Wu YH; Vainio R; Vourlidas A; Plotnikov I; Afanasiev A; Onel H (IOP PUBLISHING LTD, 2022)
We develop and exploit a new catalog of coronal pressure waves modeled in 3D to study the potential role of these waves in accelerating solar energetic particles (SEPs) measured in situ. Our sample comprises modeled shocks and SEP events detected during solar cycle 24 observed over a broad range of longitudes. From the 3D reconstruction of shock waves using coronagraphic observations we derived the 3D velocity along the entire front as a function of time. Combining new reconstruction techniques with global models of the solar corona, we derive the 3D distribution of basic shock parameters such as Mach numbers, compression ratios, and shock geometry. We then model in a time-dependent manner how the shock wave connects magnetically with spacecraft making in situ measurements of SEPs. This allows us to compare modeled shock parameters deduced at the magnetically well-connected regions, with different key parameters of SEPs such as their maximum intensity. This approach accounts for projection effects associated with remote-sensing observations and constitutes the most extensive study to date of shock waves in the corona and their relation to SEPs. We find a high correlation between the maximum flux of SEPs and the strength of coronal shock waves quantified, for instance, by the Mach number. We discuss the implications of that work for understanding particle acceleration in the corona.